Influence of Herbicides and Irrigation on Tall Fescue Shoot and Root Growth - Dani McFadden; Jack Fry; Steve Keeley; Jared Hoyle (Kansas Agricultural Experiment Station Research Reports, 2021)
When turfgrass stands are under renovation, a common problem is removing weeds prior to seeding because seedling turf does not emerge and compete well with weeds that are present. However, most herbicide labels recommend waiting for a defined period of time prior to seeding. If seeding is done prior to the date prescribed on the herbicide label, seed germination and seedling growth may be inhibited. A greenhouse study was conducted to determine the effects of irrigation prior to seeding on seedling growth after herbicide application. Overall, irrigation had no influence on the impact of herbicides on shoot or root growth in these greenhouse experiments. Our results suggest delaying seeding by more than 3 days after the application of 2,4-D + MCPP + dicamba (Trimec Classic) may not be necessary.
Keywords: tall fescue; irrigation; seeding; herbicide application